Conspicuous Travel: Consuming and Sharing on Facebook - Arda, Zeynep (Historia y Comunicación Social, 2014)
The self-conscious individual of our contemporaneity is excessively conscious of her/his appearance or manner, as it is constantly reflected in the digital mirrors of the online social network. We tend to build our images in the way that we want others to see us, hence slowly we losing the boundary between our images and our identities. Within this perspective, traveling also becomes an item of conspicuous consumption – and the online social network, its display.